Detection of vulnerabilities in smart contracts specifications in ethereum platforms - Argañaraz, Mauro (2020)
Ethereum is the principal ecosystem based on blockchain that provides a suitable environment for coding and executing smart contracts, which have been receiving great attention due to the commercial apps and among the scientific community. The process of writing secure and well performing contracts in the Ethereum platform is a major challenge for developers. It consists of the application of non-conventional programming paradigms due to the inherent characteristics of the execution of distributed computing programs. Furthermore, the errors in the deployed contracts could have serious consequences because of the immediate linkage between the contract code and the financial transactions. The direct handling of the assets means that the errors can be more relevant for security and have greater economic consequences than a mistake in the conventional apps. In this paper, we propose a tool for the detection of vulnerabilities in high-level languages based on automatized static analysis.